Democratic mechanisms: double majority rules and flexible agenda costs - Gersbach, Hans (CESifo working papers, 2002)
We introduce democratic mechanisms where individual utilities are not observable by other people at the legislative stage. We show that the combination of three rules can yield e±cient provision of public projects: first, flexible and double majority rules where the size of the majority depends on the proposal and taxed and non-taxed individuals need to support the proposal; second, flexible agenda costs where the agenda-setter has to pay a certain amount of money if his proposal does not generate enough supporting votes; third, a ban on subsidies. We also illustrate that higher dimensional uncertainty about project parameters can make it easier to achieve first-best allocations and that universal equal treatment with regard to taxation is undesirable.